Intermediate clinical endpoints: A bridge between progression‐free survival and overall survival in ovarian cancer trials. Issue 11 (21st October 2014) - Matulonis, Ursula A.; Oza, Amit M.; Ho, Tony W.; Ledermann, Jonathan A.
<x xml:space="preserve">Abstract</x> Ovarian cancer patients are usually diagnosed at an advanced stage, experience recurrence after platinum‐based chemotherapy, and eventually develop resistance to chemotherapy. Overall survival (OS), which has improved in recent years as more active treatments have been incorporated into patient care, is regarded as the most clinically relevant endpoint in ovarian cancer trials. However, although there remains a significant need for new treatments that prolong OS further without compromising quality of life, it has become increasingly difficult to detect an OS benefit for investigational treatments because of the use of multiple lines of chemotherapy to treat ovarian cancer. Progression‐free survival (PFS), which measures the time to disease progression or death, is unaffected by postprogression therapies but does not evaluate the long‐term impact of investigational treatments on tumor biology and responses to future therapies. Recent clinical trials of targeted agents in relapsed ovarian cancer have shown improvements in PFS but not OS, and this is possibly reflective of the long postprogression survival (PPS) period associated with this disease. Intermediate endpoints such as the time to second disease progression or death and the time to second subsequent therapy or death may provide supportive evidence for clinically meaningful PFS improvements and may be used to determine whether these improvements persist beyond the first disease progression and throughout subsequent lines of therapy. For clinical trials that have settings with a long PPS duration and/or involve multiple rounds of postprogression therapy, a primary endpoint of PFS supported by intermediate clinical endpoints and OS may provide a more comprehensive approach for evaluating efficacy. Cancer 2015;121:1737–1746. © 2015 American Cancer Society.